Nursing care in therapeutic plasmapheresis for late renal transplant rejection: a clinical case report - Gladys Mendoza Canaviri (Sage Sphere International Journal, 2026)
Introduction. Antibody-mediated rejection is an important cause of late kidney graft loss and may require complex immunomodulatory interventions, including therapeutic plasmapheresis. Methodology. This clinical case report describes a 45-year-old male patient with a history of deceased-donor kidney transplantation and chronic active antibody-mediated rejection, confirmed by kidney biopsy and the presence of donor-specific antibodies (DSA). Six sessions of therapeutic plasmapheresis with albumin and saline replacement were performed, followed by intravenous immunoglobulin. Comprehensive nursing assessment, clinical monitoring, and follow-up of laboratory parameters were carried out. Results. The patient tolerated the sessions without significant hemodynamic complications. Creatinine decreased from 4.8 to 3.8 mg/dL and urea from 41.7 to 37.3 mg/dL; however, the need for hemodialysis persisted. Follow-up DSA results were pending at case closure. Conclusions. During plasmapheresis, the patient remained clinically stable under specialized nursing monitoring and care. This case highlights the importance of hemodynamic surveillance, vascular access management, fluid-balance control, and early detection of adverse events during extracorporeal therapies.